2014
DOI: 10.3390/v6093450
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Identification of the First Viruses in Chia (Salvia hispanica)

Abstract: Chia (Salvia hispanica), an herbaceous plant native to Latin America, has become important in the last 20 years due to its beneficial effects on health. Here, we present the first record and identification of two viruses in chia plants. The comparison of the complete nucleotide sequences showed the presence of two viral species with the typical genome organization of bipartite New World begomovirus, identified as Sida mosaic Bolivia virus 2 and Tomato yellow spot virus, according to the ICTV taxonomic criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…In a recent experimental trial (Yeboah et al 2014) Fusarium wilt infection on chia has also been observed. Moreover, recently the presence of two viruses infecting chia plants was reported, and the infection was able to determine severe disease symptoms (Celli et al 2014). Also, Celli et al (2014) confirmed that the virus was transmitted by whiteflies, and this confirms the presence of species of Aleyrodidae family on this crop as was observed in our field trials in Southern Italy.…”
Section: Agronomic Managementsupporting
confidence: 73%
See 1 more Smart Citation
“…In a recent experimental trial (Yeboah et al 2014) Fusarium wilt infection on chia has also been observed. Moreover, recently the presence of two viruses infecting chia plants was reported, and the infection was able to determine severe disease symptoms (Celli et al 2014). Also, Celli et al (2014) confirmed that the virus was transmitted by whiteflies, and this confirms the presence of species of Aleyrodidae family on this crop as was observed in our field trials in Southern Italy.…”
Section: Agronomic Managementsupporting
confidence: 73%
“…Moreover, recently the presence of two viruses infecting chia plants was reported, and the infection was able to determine severe disease symptoms (Celli et al 2014). Also, Celli et al (2014) confirmed that the virus was transmitted by whiteflies, and this confirms the presence of species of Aleyrodidae family on this crop as was observed in our field trials in Southern Italy. Such reports of the occurrence of common diseases highlight the need to assess the appropriate control methods, including pesticides useful for the pests and pathogens identified on this crop.…”
Section: Agronomic Managementsupporting
confidence: 73%
“…Inter-species recombination is an important process during the evolution of begomoviruses and has a role in the emergence of a new strain [57]. ToYSV was the second most abundant species detected infecting pepper and was previously identified in bean and chia in Argentina [56,58]. ToYSV has a wide host range, including Solanaceae, Amaranthaceae, Fabaceae, and Lamiaceae families [59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of the complete nucleotide sequences showed the presence of two viral species with the typical genome organization of bipartite New World begomovirus, identified as Sida mosaic Bolivia virus 2 and Tomato yellow spot virus, according to the ICTV taxonomic criteria for begomovirus classification [31]. DNA-A from Sida mosaic Bolivia virus 2 exhibited 96.1% nucleotide identity with a Bolivian isolate of Sida micrantha, and Tomato yellow spot virus showed 95.3% nucleotide identity with an Argentine bean isolate.…”
Section: Description Of Begomovirus Infecting Mapsmentioning
confidence: 99%